Movies as an educational methodology. A systematic literature analysis for movie-based learning (MBL) - Díaz Herrero, Silvia (2021)
Using movies in the classroom is not a new proposal, but it is mostly used as an educational resource and not as a methodology capable of conducting learning so that it could be considered as an educational methodology by itself: movie-based learning (MBL). Starting this transformation requires studying the state of the art to look for previous experiences in which movies have been used in the classroom. Through a systematic literature review (articles and books published both in Spanish and English in the last twenty years) on the use of movies in the classroom, an approach to documented teaching practices was made to determine their distinctive features. Neither documented evidence on the use of movies in the classroom as a methodology nor a correlation with the improvement of students’ academic performance were found.